2019
DOI: 10.1007/s12599-019-00612-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relations Between Net Benefits of IT Projects and CIOs’ Perception of Quality of Software Development Disciplines

Abstract: Software development enterprises are under consistent pressure to improve their management techniques and development processes. These are comprised of several disciplines like requirements acquisition, design, coding, testing, etc. that must be continuously improved and individually tailored to suit specific software development project. This paper presents an evaluation approach that enables the enterprises to increase development process net benefits by improving disciplines' quality and increasing develope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The response rate was 11.2% (n = 112). Such response rates are typical for mail surveys conducted in enterprises (not only in Slovenia) [40]. Existing research demonstrated that even with response rates of around 10%, we can treat such a sample as a random sample [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…The response rate was 11.2% (n = 112). Such response rates are typical for mail surveys conducted in enterprises (not only in Slovenia) [40]. Existing research demonstrated that even with response rates of around 10%, we can treat such a sample as a random sample [41,42].…”
Section: Methodsmentioning
confidence: 99%
“…1 shows different Kano categories where y -axis measures the level of satisfaction and x -axis measures the level of requirement implementation. The original Kano model differentiates between four main types of quality categories: must-be (M), one-dimensional (O), attractive (A), and indifferent (I) ( Nayebi and Ruhe, 2019 , Vavpotič, Robnik-Šikonja, & Hovelja, 2020 ; Xu et al, 2019 ; S.; Zhao et al, 2020 ). The requirements that users expect software to have are classified as must-be .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adopting a specific methodology can determine to what extent performance goals such as cost, quality, and timeliness are achieved. 1 Existing studies show [2][3][4] that the adoption of SDMs is critical for success of development teams, but not easy to apply in practice. More specifically, it is often the case that a specific methodology is either applied partially or incorrectly, is not suitable for the enterprise due to incompatible technical characteristics, or has unsatisfactory impact on software quality, cost, and development time.…”
Section: Introductionmentioning
confidence: 99%
“…Software development methodologies (SDMs) highly influence the management of software projects. Adopting a specific methodology can determine to what extent performance goals such as cost, quality, and timeliness are achieved 1 . Existing studies show 2–4 that the adoption of SDMs is critical for success of development teams, but not easy to apply in practice.…”
Section: Introductionmentioning
confidence: 99%